PROFIL PERAN GURU SD DALAM KEGIATAN BELAJAR MENGAJAR DARI RUMAH DI MASA PANDEMI COVID-19 - Olivia Disjayanti Fauzi; Septi Budi Sartika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2020)
This research aims to describe the role of teacher’s in teaching learning activities from home in SDN Gelam 1 Candi Sidoarjo during covid-19 pandemic. The research method uses qualitative research of phenomenological types. Data collection techniques using questionnaires given to students, teachers, and parents. Data analysis techniques using the Miles & Huberman model, which includes data reduction, data display, verification and conclusions. The results showed all indicators namely planning, implementation, assessment, and allocation of learning time, meaning that all indicators of the application of learning have been achieved and there are no significant constraints during the learning activities teaching from home. This research uses a questionnaire instrument in which the questionnaire instrument is closed so that the data results are less in-depth, further research is expected to uncover the phenomenon through interview techniques.